A revitalização do Museu Histórico Municipal de Pinhal Grande - RS - Dalmolin, Cristina (2011)
This study presents the results of research conducted at the Municipal Historical Museum of Pinhal Grande. This creation is for the Professional Master's Degree thesis in Cultural Heritage at the Federal University of Santa Maria. The project proposal "Revitalization of the Historical Museum of the City of Pinhal Grande - RS" a determination came up in search of answers to the innocence of the local population of the institution and also to ensure the preservation of the important collection that the museum owns. The investigation included local history, identifying the elements of constitution and the formation of the town of Pinhal Grande as a form of understanding the part of the museum in the custody issue. Although the study of local history was possible to highlight some aspects of the 16 communities that make up the Council, stressing the strong religious presence in the management of social activities in each region. The question of heritage, identity and memory have also entered the agenda for better understanding of the heritage museum. This article is divided as follows: First, it presents a historic town of Pinhal Grande, as a way of understanding the constitution of the body. Here are some questions raised regarding the changes that the cultural heritage of Brazil had to understand and value the diversity that exists in Brazil. Finally, we describe the measures taken by the institution, the challenges encountered and to revitalize the local analysis of visual anthropology museum photographic collection